Organic silicon modified flexible thermal interface material and preparation method thereof
By using silicone modified flexible thermal interface materials in thermal composite materials, combined with alumina filler, polymer polymer matrix and interface modifier, the problems of thermal filler in thermal composite materials resulting in increased modulus and decreased adhesion performance in thermal composite materials are solved, and the excellent thermal conductivity and mechanical properties of the material are achieved.
Patent Information
- Application Number
- CN202510041324.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-05-02
AI Technical Summary
A large number of thermally conductive fillers in thermally conductive composite materials lead to an increase in the material modulus and a decrease in adhesion performance.
Silicone modified flexible thermal interface materials, including alumina fillers, polymer polymer matrix and interface modifiers, are used to adjust the flexibility and bonding properties of the material through step-by-step polymerization method and the use of interface modifiers.
It realizes excellent thermal conductivity and mechanical properties of the material, reduces costs, and improves interface thermal resistance, and is suitable for heat dissipation problems of electronic equipment and 5G base stations.
Smart Images

Figure BDA0005237042020000051
Abstract
Description
Technical Field
[0001] The invention relates to a flexible thermal interface material and a preparation method thereof, belonging to the technical field of thermal conductive material preparation. Background Art
[0002] With the leapfrog progress of science and technology, electronic products are constantly developing towards intelligence and miniaturization, and heat dissipation has gradually become the main factor affecting the performance and service life of electronic devices. The study of thermal conductive materials has attracted the attention of multidisciplinary researchers. The heat output of electronic components, characterized by calorific value and heat flux density, has increased significantly. The accumulation of waste heat inside the device has a significant impact on the performance and life of electronic equipment, which poses new challenges to the development of thermal interface materials (TIMs). There are inevitable gaps between the device and the thermal conductive material, which increases the overall thermal resistance and limits the heat dissipation. This poses new challenges to the development of thermal interface materials. In order to ensure the reliable operation of electronic equipment, there is an urgent need for a general, commonly used, and flexible thermal interface material with excellent thermal conductivity. Thermal interface materials are used to fill the gap between heat sources and heat sinks, and the thermal conductivity of these materials is an important feature that developers in this field pay attention to.
[0003] In wearable and soft electronic devices, solving the problem of thermal transfer at the interface requires interface materials that meet the dual requirements of adhesion and thermal conductivity. TIMs with high thermal conductivity but weak adhesion are repeatedly bent and compressed in flexible devices. Mechanical stress leads to interruption of close contact, resulting in gaps between interfaces and reducing heat transfer efficiency. Researchers have tried to use thermally conductive fillers in combination with elastic adhesives to improve the adhesion of the interface. At the same time, strong chemical bonds (especially hydrogen bonds and boron ester bonds) are integrated into the polymer matrix through grafting or copolymerization to improve the adhesion energy of thermal interface materials. These strategies contribute to the long-term stability of thermal interface materials and help reduce the contact thermal resistance at the solid interface, thereby improving the overall thermal performance. In the field of wearable device applications, TIMs are subjected to various stresses (bending, stretching and compression) during operation, which requires TIMs to have high flexibility and toughness. However, in order to improve the thermal conductivity of the material, a large amount of fillers must be added, which will lead to an increase in the material's modulus and a decrease in adhesion performance. Striking a balance between these conflicting properties poses a major challenge to the development of future thermal interface materials. Summary of the invention
[0004] The present invention aims to solve the problem of increased material modulus and decreased bonding performance caused by a large amount of thermally conductive fillers in a thermally conductive composite material, and further proposes an organosilicon-modified flexible thermal interface material and a preparation method thereof.
[0005] The technical solution adopted by the present invention to solve the above problems is: the organosilicon modified flexible thermal interface material of the present invention comprises aluminum oxide filler, a high molecular polymer matrix and an interface modifier.
[0006] Furthermore, the weight proportions of the alumina filler, the polymer matrix and the interface modifier are: 50-90 parts of the alumina filler, 10-50 parts of the polymer matrix, and 1-5 parts of the interface modifier.
[0007] Furthermore, the polymer body is composed of hydroxyl-terminated polysiloxane (M n =2300), polyether polyol (M n =1000), castor oil (M n =1024), isophorone diisocyanate and tea polyphenols.
[0008] Furthermore, the hydroxyl-terminated polysiloxane (M n =2300), polyether polyol (M n =1000), castor oil (M n =1024), the mass fractions of isophorone diisocyanate and tea polyphenols are: hydroxyl-terminated polysiloxane (M n =2300) 30-60 parts, polyether polyol (M n =1000) 20-40 parts, castor oil (M n =1024) 20-40 parts, isophorone diisocyanate 20-30 parts, tea polyphenols 1-10 parts.
[0009] Furthermore, the alumina filler is composed of one or more of alumina with a particle size of 50 μm, 40 μm, 30 μm, 20 μm, 10 μm, 5 μm, and 2 μm.
[0010] Furthermore, the interface modifier is composed of one or more of dodecyltrimethoxysilane, stearic acid, aminopropyltriethoxysilane, lauric acid hard ether ester, and aluminate coupling agent.
[0011] Furthermore, the mass ratio of the interface modifier to the alumina filler is 1%-5%.
[0012] The steps of the method for preparing the organosilicon-modified flexible thermal interface material of the present invention include:
[0013] Step 1: pre-treat the prepolymer by vacuum dehydration, gradually add isocyanate and chain extender by distributed polymerization, and stir at a constant speed at 80° C. until the reaction is completed;
[0014] Step 2, high-speed stirring is performed on the alumina filler, and an interface modifier dissolved in an organic solvent is sprayed into the filler during high-speed stirring, so that the interface modifier is evenly distributed in the filler;
[0015] Step 3, adding the interface modified alumina filler to the synthesized polymer solution, and stirring at high speed until the filler is evenly distributed;
[0016] Step 4: Place the stirred material in a polytetrafluoroethylene mold, remove bubbles in a vacuum oven, and fully cure it in an 80° C. oven for 24 hours to obtain the flexible thermal interface composite material.
[0017] Furthermore, the organic solvent of the interfacial modifier is composed of one or more of ethanol, methanol, and deionized water.
[0018] Furthermore, the curing temperature of the polymer melt and the composite thereof is 60° C.-120° C., and the drying time is 24 hours.
[0019] The beneficial effects of the present invention are:
[0020] 1. The present invention endows the material with excellent thermal conductivity and mechanical properties, while reducing the cost, so that the elastomer composite material has higher thermal conductivity and excellent interface thermal resistance, and proposes new ideas and solutions for the heat dissipation of electronic equipment and the heat dissipation of 5G base station construction. The composite material obtained by the present invention can quickly dissipate heat to a larger area, with better heat dissipation effect and faster response.
[0021] 2. The present invention adopts a step-by-step polymerization method to synthesize a polyphenol-rich adhesive elastomer, and controls the flexibility of the material by adjusting the ratio of the soft segment and the hard segment. The synthesized composite material strikes a balance between adhesive properties and compliance properties. The excellent adhesiveness and flexibility of the material simplifies the multilayer structure of flexible electronic devices and provides stability for their long-term use.
[0022] 3. The process flow of the present invention is simple and convenient, has low requirements on process conditions, and is easy to implement. Example
[0023] Example 1
[0024] The pretreated polypropanol (10g, 10mmol) and the terminal hydroxyl polydimethylsiloxane (6.9g, 3mmol) were mixed in a 250ML four-necked flask in a predetermined molar ratio. Under vacuum conditions at 60°C, mechanical stirring was performed for 2h to further remove the moisture in the system. After the mixture was cooled to 60°C, isophorone diisocyanate (6.4g, 29mmol) and 0.1wt% dibutyltin disalicylate (DBTDL) were added to the flask, heated to 60°C under a nitrogen atmosphere and mechanically stirred for 2h to obtain a prepolymer. When the system temperature dropped to 25°C, castor oil (10.24g, 10mmol) was added to the prepolymer and continued to stir for 3h. Tea polyphenols (0.11g, 0.25mmol) were dissolved in DMF solvent (5ML), added to the reaction product, and stirred thoroughly for 3h to obtain a viscous liquid.
[0025] The obtained solution was poured onto a polytetrafluoroethylene mold and placed in a vacuum oven at 90° C. to cure to form a film. The film was taken out from the mold to obtain a polyurethane elastomer PUR-SI0.3.
[0026] Example 2
[0027] The pretreated polypropanol (10g, 10mmol) and the terminal hydroxyl polydimethylsiloxane (6.9g, 3mmol) were mixed in a 250ML four-necked flask in a predetermined molar ratio. Under vacuum conditions at 60°C, mechanical stirring was performed for 2h to further remove moisture from the system. After the mixture was cooled to 60°C, isophorone diisocyanate (6.22g, 28mmol) and 0.1wt% dibutyltin disalicylate (DBTDL) were added to the flask, heated to 60°C under a nitrogen atmosphere and mechanically stirred for 2h to obtain a prepolymer. When the system temperature dropped to 25°C, castor oil (10.24g, 10mmol) was added to the prepolymer and continued to stir for 3h. Tea polyphenols (0.11g, 0.25mmol) were dissolved in DMF solvent (5ML), added to the reaction product, and stirred thoroughly for 3h to obtain a viscous liquid.
[0028] The obtained solution was poured onto a polytetrafluoroethylene mold and placed in a vacuum oven at 90° C. to solidify to form a film. The film was taken out from the mold to obtain a polyurethane elastomer PUR-SI0.2.
[0029] Example 3
[0030] The pretreated polypropanol (10g, 10mmol) and the terminal hydroxyl polydimethylsiloxane (6.9g, 3mmol) were mixed in a 250ML four-necked flask in a predetermined molar ratio. Under vacuum conditions at 60°C, mechanical stirring was performed for 2h to further remove the moisture in the system. After the mixture was cooled to 60°C, isophorone diisocyanate (6.4g, 29mmol) and 0.1wt% dibutyltin disalicylate (DBTDL) were added to the flask, heated to 60°C under a nitrogen atmosphere and mechanically stirred for 2h to obtain a prepolymer. When the system temperature dropped to 25°C, castor oil (10.24g, 10mmol) was added to the prepolymer and continued to stir for 3h. Tea polyphenols (0.11g, 0.25mmol) were dissolved in DMF solvent (5ML), added to the reaction product, and stirred thoroughly for 3h to obtain a viscous liquid.
[0031] The alumina filler was stirred at high speed, and aminopropyl triethoxysilane dissolved in ethanol solution was sprayed during high-speed stirring to make the interface modifier evenly distributed in the filler; Al2O3 powder (50.48g) was added according to the corresponding mass to prepare the PUR-SI solution, and then the filler was dispersed in the uncured elastomer with a magnetic stirrer. The polyurethane elastomer composite was placed in an oven at 80°C for curing for 24 hours and cooled to room temperature.
[0032] Example 4
[0033] The pretreated polypropanol (10g, 10mmol) and the terminal hydroxyl polydimethylsiloxane (6.9g, 3mmol) were mixed in a 250ML four-necked flask in a predetermined molar ratio. Under vacuum conditions at 60°C, mechanical stirring was performed for 2h to further remove the moisture in the system. After the mixture was cooled to 60°C, isophorone diisocyanate (6.4g, 29mmol) and 0.1wt% dibutyltin disalicylate (DBTDL) were added to the flask, heated to 60°C under a nitrogen atmosphere and mechanically stirred for 2h to obtain a prepolymer. When the system temperature dropped to 25°C, castor oil (10.24g, 10mmol) was added to the prepolymer and continued to stir for 3h. Tea polyphenols (0.11g, 0.25mmol) were dissolved in DMF solvent (5ML), added to the reaction product, and stirred thoroughly for 3h to obtain a viscous liquid.
[0034] The alumina filler was stirred at high speed, and aminopropyl triethoxysilane dissolved in ethanol solution was sprayed during high-speed stirring to make the interface modifier evenly distributed in the filler; Al2O3 powder (78.52g) was added according to the corresponding mass to prepare the PUR-SI solution, and then the filler was dispersed in the uncured elastomer with a magnetic stirrer. The polyurethane elastomer composite was placed in an oven at 80°C for curing for 24 hours and cooled to room temperature.
[0035] Example 5
[0036] The pretreated polypropanol (10g, 10mmol) and the terminal hydroxyl polydimethylsiloxane (6.9g, 3mmol) were mixed in a 250ML four-necked flask in a predetermined molar ratio. Under vacuum conditions at 60°C, mechanical stirring was performed for 2h to further remove the moisture in the system. After the mixture was cooled to 60°C, isophorone diisocyanate (6.4g, 29mmol) and 0.1wt% dibutyltin disalicylate (DBTDL) were added to the flask, heated to 60°C under a nitrogen atmosphere and mechanically stirred for 2h to obtain a prepolymer. When the system temperature dropped to 25°C, castor oil (10.24g, 10mmol) was added to the prepolymer and continued to stir for 3h. Tea polyphenols (0.11g, 0.25mmol) were dissolved in DMF solvent (5ML), added to the reaction product, and stirred thoroughly for 3h to obtain a viscous liquid.
[0037] The alumina filler was stirred at high speed, and aminopropyl triethoxysilane dissolved in ethanol solution was sprayed during high-speed stirring to make the interface modifier evenly distributed in the filler; Al2O3 powder (134.60g) was added according to the corresponding mass to prepare the PUR-SI solution, and then the filler was dispersed in the uncured elastomer with a magnetic stirrer. The polyurethane elastomer composite was placed in an oven at 80°C for curing for 24 hours and cooled to room temperature.
[0038] Example 6
[0039] The pretreated polypropanol (10g, 10mmol) and the terminal hydroxyl polydimethylsiloxane (6.9g, 3mmol) were mixed in a 250ML four-necked flask in a predetermined molar ratio. Under vacuum conditions at 60°C, mechanical stirring was performed for 2h to further remove the moisture in the system. After the mixture was cooled to 60°C, isophorone diisocyanate (6.4g, 29mmol) and 0.1wt% dibutyltin disalicylate (DBTDL) were added to the flask, heated to 60°C under a nitrogen atmosphere and mechanically stirred for 2h to obtain a prepolymer. When the system temperature dropped to 25°C, castor oil (10.24g, 10mmol) was added to the prepolymer and continued to stir for 3h. Tea polyphenols (0.11g, 0.25mmol) were dissolved in DMF solvent (5ML), added to the reaction product, and stirred thoroughly for 3h to obtain a viscous liquid.
[0040] The alumina filler was stirred at high speed, and aminopropyl triethoxysilane dissolved in ethanol solution was sprayed during high-speed stirring to make the interface modifier evenly distributed in the filler; Al2O3 powder (206.71g) was added according to the corresponding mass to prepare the PUR-SI solution, and then the filler was dispersed in the uncured elastomer with a magnetic stirrer. The polyurethane elastomer composite was placed in an oven at 80°C for curing for 24 hours and cooled to room temperature.
[0041] The performance tests of the thermally conductive composite materials obtained in Examples 1 to 6 are shown in the following table:
[0042]
[0043] The silicone modified flexible thermal interface materials prepared in Examples 1 to 6 ensure long-term reliability. Given its multifunctional properties, this advanced thermally conductive composite material shows great application potential in thermal interface materials for flexible electronics, electronic packaging, and organic substrates.
[0044] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent replacement and improvement made to the above embodiments without departing from the content of the technical solution of the present invention, based on the technical essence of the present invention, within the spirit and principles of the present invention, still fall within the protection scope of the technical solution of the present invention.
Claims
1. A silicone modified flexible thermal interface material, characterized in that: It comprises aluminum oxide filler, high molecular polymer matrix and interface modifier.
2. The organosilicon-modified flexible thermal interface material according to claim 1, characterized in that: The weight proportions of the alumina filler, the polymer matrix and the interface modifier are as follows: 50-90 parts of the alumina filler, 10-50 parts of the polymer matrix and 1-5 parts of the interface modifier.
3. The organosilicon-modified flexible thermal interface material according to claim 1, characterized in that: The polymer body is composed of hydroxyl-terminated polysiloxane (M n =2300), polyether polyol (M n =1000), castor oil (M n =1024), isophorone diisocyanate and tea polyphenols.
4. The organosilicon-modified flexible thermal interface material according to claim 3, characterized in that: Hydroxyl terminated polysiloxane (M n =2300), polyether polyol (M n =1000), castor oil (M n =1024), the mass fractions of isophorone diisocyanate and tea polyphenols are: hydroxyl-terminated polysiloxane (M n =2300) 30-60 parts, polyether polyol (M n =1000) 20-40 parts, castor oil (M n =1024) 20-40 parts, isophorone diisocyanate 20-30 parts, tea polyphenols 1-10 parts.
5. The organosilicon-modified flexible thermal interface material according to claim 1, characterized in that: The alumina filler is composed of one or more of alumina with a particle size of 50 μm, alumina with a particle size of 40 μm, alumina with a particle size of 30 μm, alumina with a particle size of 20 μm, alumina with a particle size of 10 μm, alumina with a particle size of 5 μm, and alumina with a particle size of 2 μm.
6. The organosilicon-modified flexible thermal interface material according to claim 1, characterized in that: The interface modifier is composed of one or more of dodecyl trimethoxy silane, stearic acid, aminopropyl triethoxy silane, lauric acid hard ether ester and aluminate coupling agent.
7. The organosilicon-modified flexible thermal interface material according to claim 1, characterized in that: The mass ratio of the interface modifier to the alumina filler is 1%-5%.
8. A method for preparing a silicone-modified flexible thermal interface material, characterized in that: The specific steps include: Step 1: pre-treat the prepolymer by vacuum dehydration, gradually add isocyanate and chain extender by distributed polymerization, and stir at a constant speed at 80° C. until the reaction is completed; Step 2, high-speed stirring is performed on the alumina filler, and an interface modifier dissolved in an organic solvent is sprayed into the filler during high-speed stirring, so that the interface modifier is evenly distributed in the filler; Step 3, adding the interface modified alumina filler to the synthesized polymer solution, and stirring at high speed until the filler is evenly distributed; Step 4: Place the stirred material in a polytetrafluoroethylene mold, remove bubbles in a vacuum oven, and fully cure it in an 80° C. oven for 24 hours to obtain the flexible thermal interface composite material.
9. The method for preparing a silicone-modified flexible thermal interface material according to claim 8, characterized in that: The organic solvent of the interface modifier is composed of one or more of ethanol, methanol and deionized water.
10. The method for preparing a silicone-modified flexible thermal interface material according to claim 8, characterized in that: The curing temperature of the polymer melt and its composite is 60°C-120°C, and the drying time is 24 hours.